Molecular characterization of fluoroquinolone-resistant Escherichia coli from broiler breeder farms - Seo, Kwang Won (Poult Sci, 2021)
Fluoroquinolones (FQs) have been used effectively antimicrobial agents of choice for treatment of various infections caused by E. coli and FQs-resistance of E. coli from broiler breeders has been implicated in its vertical transmission to their offspring. The objective of this study investigated the phenotypic and genotypic characteristics of FQ-resistant E. coli isolates from broiler breeder farms in Korea. A total of 106 FQ-resistant E. coli isolates were tested in this study and all isolates had mutations in quinolone resistance determining regions; all (100%) had mutations in gyrA, 89 (84.0%) had mutations in parE, 8 (7.5%) isolates showed the mutations with parC and parE, and none had mutations in gyrB. The predominant mutation type was double mutation in gyrA (S83L and D87N), and all FQ-resistant E. coli isolates that had mutations in parC or parE also had double mutations in gyrA. Especially, FQ-resistant E. coli isolates which possessed double mutations in gyrA in combination with double mutations in parC or single mutations in both parC and parE were shown high levels of minimum inhibitory concentrations rage. Of the 23 plasmid-mediated quinolone resistance (PMQR)-positive E. coli isolates, qnrS was detected in 10 (9.4%) isolates, and followed by qnrA (7 isolates, 6.6%), qnrB (4 isolates, 3.8%), and aac(6′)-Ib-cr (2 isolates, 1.9%). Sixteen (69.6%) of the 23 PMQR-positive E. coli isolates harbored class 1 integrons with four different gene cassette arrangements and total of 9 plasmid replicon types were also identified in 23 PMQR-positive E. coli isolates. This is the first study to investigate the prevalence and characteristics of FQ-resistant and PMQR-positive E. coli isolated from the broiler breeder in Korea; it supports that constant monitoring and studies at the broiler breeder level are required to prevent the pyramidal transmission of FQ-resistant E. coli.